Treatment of Advanced NSCLC Patients with an Anti-Idiotypic NeuGcGM3-Based Vaccine: Immune Correlates in Long-Term Survivors - Zaima Mazorra; Haslen H. Cáceres-Lavernia; Elia Nenínger-Vinageras; Leslie M. Varona-Rodríguez; Carmen Elena Viada; Zuyen González; Nely Rodríguez-Zhurbenko; Anne-Christine Thierry; Gisela María Suarez-Formigo; Yendry Ventura-Carmenate; Petra Baumgaertner; Sara Trabanelli; et al. (Biomedicines)
Background: Racotumomab-alum is an anti-idiotype vaccine targeting the NeuGcGM3 tumor-associated ganglioside. Clinical trials in advanced cancer patients have demonstrated low toxicity, high immunogenicity and clinical benefit. The goal of this study was to identify circulating biomarkers of clinical outcome. Methods: Eighteen patients with stage IIIb/IV non-small-cell lung cancer (NSCLC) were injected with racotumomab-alum as switch maintenance therapy after first-line chemotherapy. Treatment was administered until severe performance status worsening or toxicity. The frequencies of innate and adaptive lymphocytes were assessed by flow cytometry. Circulating factors were measured using multi-analyte flow assay kits. Results: The median overall survival was 16.5 months. Twenty-seven percent of patients were classified as long-term survivors. Patients with lower baseline frequencies of CD4+Tregs and central memory (CM) CD8+T cells displayed longer survival rates. Furthermore, higher baseline frequencies of NKT cells and a high CD8+T/CD4+Treg ratio were associated with longer survival. Interestingly, patients with significantly lower levels of effector memory (EM) CD8+T cells survived longer. The levels of NKT cells and terminal effector memory (EMRA) CD8+T cells were higher in long-term survivors in comparison with short-term survivors in post-immune samples. As expected, the ratio of CD8+T/CD4+Tregs showed significantly higher values during treatment in patients with clinical benefits. Regarding serum factors, pro-tumorigenic cytokines significantly increased during treatment in poor survivors. Conclusions: In advanced NSCLC patients receiving racotumomab-alum vaccine, longer survival could be associated with a unique profile of circulating lymphocyte subsets at baseline and during treatment. Additionally, certain pro-tumor-related cytokines increased in short-term survivors. These results should be confirmed in larger randomized clinical trials. This clinical trial was registered in the Cuban Clinical Trials Register (RPCE00000279).